ANALISIS KUALITAS PRODUK PACKAGING PLASTIK DENGAN PENDEKATAN METODE POKA YOKE - Faizal, Achmad (International Journal of Psychosocial Rehabilitation, 2020)
B69.PRINT is a small micro-enterprises (MSMES) that manufactures various types of packaging, the company realized to compete in business competition then business actors must improve the quality of their products and services to maintain the trust of the consumers. The company currently has problems in its product results, which is still a product that does not meet the quality standards, so that it can affect consumer interest and the marketing process so disturbed. This research is done to reduce the errors that underlie waste and can provide solutions to effective and efficient problems. The problem now faced by the company is the quality of the product, it is seen from several products defect to exceed the determination of the tolerance limit of 1.5%. Quality is the main factor that needs to be noticed in B69. Print, therefore, required a tool or method to suppress the number of defects of the product to Zero Defect. The tools or research methods that are done in case studies are using Pareto Diagram, Fishbone Diagram, and Poka Yoke method to define the mistakes caused by Human Error and can provide proposals for improvement. Based on research that has been conducted known defect priorities using Pareto Diagram is located on the type of Screen-Printing Defect (A) with an average percentage throughout the year 2019 of 1.91% which occurs due to overproduction over the capacity of B69 production capability. Print each month reaches 13,104 Pcs. Fishbone Diagram shows the magnitude of demand often lowers the focus of workers due to rush chasing deadline without regard to product quality. The results of Poka Yoke analysis also shows there is still "step process not done" with the highest score of 8 points, then the author team proposed three types of improvements started from the Warning function as a tool to ensure, Control tools to show the order of work, and Shut Down to show the time of the worker process.